MODELING THE THERMAL EFFECT ON DEPOSITS WITH HIGH-VISCOSITY OILS - Smolovyk, L. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The reasons for using thermal methods to increase oil well productivity in conditions of acute shortage of hydrocarbon raw materials are described. The introduction of cyclic in-situ combustion in fields with a sparse well layout is proposed. To evaluate the effectiveness of the cyclic ICF process and its technological characteristics, mathematical modeling of the process was performed. A mathematical model was developed, described by a system of eight equations with eight unknowns, which are functions of distance and time with corresponding initial and boundary conditions. The calculation of heat exchange between the heat carrier and the skeleton of the porous medium was performed based on a two-temperature model. The mathematical model itself was developed with an emphasis on the temperature conditions in the formation and the phenomena associated with temperature increase. According to the calculation results, depending on the characteristics of oil and productive deposits, there are optimal values for the flow rate and time of air injection and the total volume of air injected, at which the maximum technological effect is achieved in terms of total oil production and the duration of the well's operation at an increased flow rate. The studies conducted indicate the high efficiency of the cyclic intra-formation combustion process.